Toponyms with the root *baz - Nikić, Biljana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
During the research, it has been considered which toponyms on the Balkan Peninsula are named after the plant elder (Proto-Slavic root * baz). Using etymology dictionaries, as well as the list of settlements of the Republic of Serbia, we have found twenty-three such toponyms. All the places named by them are situated in the mountain region, which is exactly the area where the elders grow. Phonetic variations which exist among the excerped toponyms are differently interpreted by etymologists. Most of the settlements are very old, which confirms the Proto-Slavic origin and refutes the interpretation given in the folk tales. Trojan/Trajan is associated with the elder − in the story about the emperor with the goat’s ears, the elder reveals the secret about the emperor’s oddness. In the research, the emperor Trojan/Trajan is associated with Triglav, the Slavic god symbolized by the elder.